Target specificity of different phytochemicals in preventing the binding of OxLDL To LOX-1: An in silico approach - Alam, Ratul; Bin Aziz, Nasif (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.